급성 견봉쇄골 관절 손상에서의 Hook 금속판 고정술: 112명의 환자 결과 분석 및 금속판 종류와 오구쇄골 인대 봉합술 시행 여부에 따른 차이 평가 - 황재광(Jae Kwang Hwang); 이기원(KiWon Lee); 배주열(Joo-Yul Bae); 최신우(Shinwoo Choi); 조성윤(Sungyoon Cho); 최한석(Han Suk Choi) (The journal of the Korean Orthopaedic Association, 2024)
목적: 본 연구에서는 급성 견봉쇄골 관절 손상에서 Hook 금속판을 이용한 수술적 치료의 임상 결과 및 방사선학적 결과를 평가하고, 금속판 종류와 오구쇄골(coracoclavicular, CC) 인대 봉합술 시행 여부에 따른 차이를 평가하고자 하였다. 대상 및 방법: 2008년 2월부터 2022년 11월까지 급성 견봉쇄골 관절 손상에 대해 Hook 금속판을 이용한 고정술을 시행 받은112명의 환자를 대상으로 후향적으로 분석하였다. Depuy Synthes Hook 금속판을 이용한 환자군(76명)과 ARIX Hook 금속판을 이용한 환자군(36명), Hook 금속판 고정술에 오구쇄골 인대 봉합술을 추가한 환자군(42명)과 Hook 금속판 고정술만 시행한 환자군(70명)으로 각각 구분하여 분석하였다. 임상적, 방사선적 결과와 Hook 금속판의 종류 및 오구쇄골 인대 봉합술 시행 여부에 따른 차이를 visual analog scale (VAS) 통증 점수, American Shoulder and Elbow Surgeons (ASES) 점수, University of California at Los Angeles (UCLA) 점수, 오구쇄골 간 거리(coracoclavicular distance, CCD), 견봉하부 골미란 발생 유무 및 수술관련 합병증을 통해 평가하였다. 결과: 112명 환자의 내고정물 제거 수술 후 추시 기간의 중간값은 7.4개월(범위, 6.0–124.8개월)이었고, 최종 추시 ASES 점수및 UCLA 점수는 77.2±6.2, 31.8±2.3점이었으며, 건측과 비교한 오구쇄골 간 거리는 115.5%±28.9%였다. Depuy Synthes와ARIX Hook 금속판군 간 및 오구쇄골 인대 봉합술 여부에 따른 VAS 점수, ASES 점수, UCLA 점수, 오구쇄골 간 거리, 견봉하부골미란 발생 유무 및 수술관련 합병증의 통계적인 차이는 없었다. 결론: 급성 견봉쇄골 관절 손상에서 Hook 금속판을 이용한 내고정술은 임상적 및 방사선학적으로 우수한 결과를 보여 유용한 수술 방법 중 하나로 생각된다. Hook 금속판의 종류와 오구쇄골 인대 봉합 여부에 따른 결과 차이는 없었다. Purpose: This study is evaluated the clinical and radiological outcomes of Hook plate fixation in acute acromioclavicular (AC) joint injuries and the differences according to the type of plate and whether coracoclavicular (CC) ligament repair had been performed. Materials and Methods: Between February 2008 and November 2022, 112 patients treated with a Hook plate for acute AC joint injuries were analyzed retrospectively. The patients were categorized into DePuy Synthes (n=76) and ARIX Hook plate group (n=36), Hook plate with CC ligament repair group (n=42) and Hook plate fixation only group (n=70). The clinical and radiologic outcomes of Hook plate fixation were evaluated by analyzing the visual analog scale (VAS) pain score, American Shoulder and Elbow Surgeons (ASES) score, University of California at Los Angeles (UCLA) score, coracoclavicular distance (CCD), subacromial erosion and associated surgical complications depending on the different types of Hook plate (DePuy Synthes vs. ARIX clavicle system) and the application of additional CC ligament repair. Results: The median follow-up period after implant removal for the 112 patients was 7.4 months (range, 6.0–124.8 months). The ASES and UCLA scores at the final follow-up were 77.2±6.2 and 31.8±2.3, respectively, and the CCD was 115.5%±28.9% compared to the unaffected side. There were no significant differences in the final VAS score, ASES score, UCLA score, CCD, subacromial erosion and surgical complications between the DePuy Synthes and ARIX Hook plate groups. In addition, there was no difference depending on whether CC ligament repair had been performed. Conclusion: Hook plate fixation in acute AC joint injuries showed good clinical and radiological results. It is considered a good surgical method, and there was no difference in the results depending on plate type and CC ligament repair. KCI Citation Count: 0